Pengaruh Pertumbuhan Penjualan, Struktur Aktiva Dan Profitabilitas Terhadap Struktur Modal Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Sub Sektor Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesiapada Tahun 2019 -2023 - Tazkia Matura Panggabean; akmal huda; muhammad rizal (Jurnal Ilmu Ekonomi dan Bisnis, 2024)
The problem in this study is that many companies in the telecommunication sub-sector have a higher level of debt than equity, which directly impacts the company's operational sustainability and capital structure. This study aims to examine the influence of sales growth, asset structure, and profitability, as well as to test firm size as a moderating variable on the company's capital structure. The population of this study consists of telecommunication sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sampling technique used is purposive sampling, with a total of 50 research samples. Data were collected by downloading annual reports and sustainability reports from the official IDX website and the respective company websites. The data analysis technique used is multiple regression analysis with a moderating variable. The results of the study indicate that, partially, asset structure influence capital structure, while sales growth and profitability has no effect. Simultaneously, the three independent variables affect the capital structure. Firm size moderates the influence of asset structure on capital structure but does not moderate the effect of sales growth and profitability on capital structure